Mengidentifikasi Kebutuhan Sistem Informasi Akademik Krs (Kartu Rencana Studi) Menggunakan Teknologi Blockchain Pada Universitas Bina Darma Palembang - Gilang Ramanda Purba (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2021)
The advancement of a more sophisticated period forces us to keep up with the times, especially as we approach the fourth industrial revolution, in which practically all activities rely on technological systems to assist and facilitate people in their daily lives. In the same way, an educational institution must stay up with contemporary events. Blockchain is one of the various technical systems that have arisen in recent years. Blockchain is a technology system for recording digital transaction data that is connected by cryptography and managed by a collection of computers.